Consumer preferences for pork attributes related to traceability, information certification, and origin labeling: Based on China's Jiangsu Province. Issue 3 (19th April 2017) - Wu, Linhai; Gong, Xiaoru; Qin, Shasha; Chen, Xiujuan; Zhu, Dian; Hu, Wuyang; Li, Qingguang
Abstract: In this study, 110 consumers in Wuxi, China's Jiangsu Province were surveyed for their preferences for traceable pork in a real choice experiment. Using random parameters logit and latent class logit models, results revealed that consumers had the highest willingness to pay (WTP) for government certification of traceability information authenticity. Consumers also had higher WTP for origin labeling compared to uncertified traceability information. Moreover, traceability to slaughter and processing was viewed as a substitute for local farming labeling and complement to non‐local farming labeling. Despite the heterogeneity among consumer groups, all consumers had some positive WTP for the local farming labeling attribute of traceable pork. Therefore, it is beneficial to include origin labeling in the traceable food attribute systems during the initial construction of traceable food markets in China.